Vacationland : tourism and environment in the Colorado High Country - Philpott, William, 1970- (Weyerhaeuser environmental book., 2013)
Peopled with colorful characters, richly evocative of the Rocky Mountain landscape, this book asks readers to consider how profoundly tourism changed Colorado and America and to grapple with both the potential and the problems of our familiar ways of relating to environment, nature, and place.